Personal efficiencyof management work according to studies of time - Bácsné Bába, Éva (Acta Scientiarum Socialium, 2011)
Personal efficiency of management work according to studies of time In my research I approach the role of time factor in management work otherwise than the conventional time management researches do that. The main objectives of my research are the following: To explore the function of time in management work; and to prove that time as a resource can serve to improve the effectiveness of the management and the company. I would like to explore the opinions of managers on the time factor and on whether time effectiveness can be improved. I show opinion of managers of organisations of different sizes (micro, small, medium and large) and forms (joint-stock company, ltd., shared joint-stock company, co-operative society, and other), and of organisations which have been transformed and which have not. I present time management practice in the managing activities of managers of different ages, sexes, qualifications, positions and working hours. I reveal, according to the managers’ valuation, what managing tasks are emphasised and which are the ones that remain in the background, i.e. what rearrangements take place in managing activities nowadays. I would like to make establishments and conclusions, on the basis of researches, which help the heads of organisations to make both their personal and their compa-ny’s time management more effective.
Keywords: personal efficiency; time factor; managing tasks; time managment